2022
DOI: 10.1177/10406387221094272
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication of llamas by Astragalus punae in Argentina

Abstract: Several plants that contain indolizidine alkaloids, including swainsonine, are toxic to livestock, causing dysfunctional lysosomes and storage disease. Swainsonine induces a neurovisceral disease, known as locoism, in sheep, goats, and cattle, which occurs in several parts of the world, including, but not limited to, the western United States, China, and parts of Australia. In South America, locoism has been described in the Andean region of Argentina affecting sheep, cattle, and llamas. Intoxication by consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…M. Johnston (1947: 389) has been reported as a toxic species for llamas (Camelidae) in South America (Marin et al 2022). Those species of Astragalus containing nitrotoxins kill or permanently cripple thousands of sheep and cattle annually (Williams & Baneby 1977) and therefore have a serious economic impact on the livestock industry.…”
Section: Importance Of the Speciesmentioning
confidence: 99%
“…M. Johnston (1947: 389) has been reported as a toxic species for llamas (Camelidae) in South America (Marin et al 2022). Those species of Astragalus containing nitrotoxins kill or permanently cripple thousands of sheep and cattle annually (Williams & Baneby 1977) and therefore have a serious economic impact on the livestock industry.…”
Section: Importance Of the Speciesmentioning
confidence: 99%
“…Locoweed, a plant species with a global distribution ( 1 ), has been documented in various countries including the United States ( 2 ), Brazil ( 3 ), Argentina ( 4 ), Australia ( 5 ), and China ( 6 ). The earliest instances of poisonous plant poisoning diseases in the western region of the country were documented in the United States in 1873 ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have unequivocally demonstrated that SW can inflict damage on multiple organs, encompassing the cerebrum, cerebellum, liver, kidneys, pancreas, and thyroid gland ( 1 ). Notably, renal injury is observed at relatively lower dosages or at earlier time points ( 4 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation